Assembly of the replication initiation complex on SV40 origin DNA - Simmons, Daniel T. (Oxford University Press, 2004)
The assembly of the complex that forms over the simian virus 40 origin to initiate DNA replication is not well understood. This complex is composed of the virus-coded T antigen and three cellular proteins, replication protein A (RPA), DNA polymerase α/primase (pol/prim) and topoisomerase I (topo I) in association with the origin. The order in which these various proteins bind to the DNA was investigated by performing binding assays using biotinylated origin DNA. We demonstrate that in the presence of all four proteins, pol/prim was essential to stabilize the initiation complex from the disruptive effects of topo I. At the optimal concentration of pol/prim, topo I and RPA bound efficiently to the complex, although pol/prim itself was not detected in significant amounts. At higher concentrations less topo I was recruited, suggesting that DNA polymerase is an important modulator of the binding of topo I. Topo I, in turn, appeared to be involved in recruiting RPA. RPA, in contrast, seemed to have little or no effect on the recruitment of the other proteins to the origin. These and other data suggested that pol/prim is the first cellular protein to interact with the double-hexameric T antigen bound to the origin. This is likely followed by topo I and then RPA, or perhaps by a complex of topo I and RPA. Stoichiometric analysis of the topo I and T antigen present in the complex suggested that two molecules of topo I are recruited per double hexamer. Finally, we demonstrate that DNA has a role in recruiting topo I to the origin.